The Economics of natural resource depletion - Pearce, David W.; Rose, James, M.Sc.; U.K. Environmental Economics Study Group; Institute of Environmental Sciences (London : Macmillan, 1975)
The book is a compilation of papers given at the Conference on the Economics of Natural Resource Depletion by a number of distinguished British economist.
Slightly modified versions of papers given at a conference held at the Royal Institution, London, Jan. 16, 1974; organized by the U.K. Environmental Economics Study Group and the Institute of Environmental Sciences.
Includes bibliographical references.
gp 24/01/2019
Loans
Keywords: Natural resources